Adaptive Public Governance for Regenerative Olive Oil Tourism: A Policy Framework for Sustainable Territorial Development in Jaén, Spain - Eldon Reiner (SWATANTRA, 2025)
This article develops a public governance framework for regenerative olive oil tourism in Jaén, Spain, and positions oleotourism as a territorial policy instrument rather than a narrow market product. Spain remains one of the world’s most visited tourism economies, yet national and European tourism policy increasingly emphasises diversification, deconcentration, environmental responsibility, digital transition, and social acceptance. In this context, Jaén has a distinctive strategic asset: an extensive olive-growing landscape, a strong agrifood identity, and a growing portfolio of museums, mills, routes, viewpoints, cycling facilities, culinary experiences, and heritage narratives connected to extra virgin olive oil. The central research question is: how can public governance convert olive oil tourism into a regenerative strategy for sustainable territorial development in Jaén? Using a qualitative document-based policy analysis, the article reviews international sustainable tourism principles, European transition policy, Spanish tourism strategy, UNESCO-related heritage discourse, regional tourism materials, recent public information on Oleotour Jaén, and academic literature on olive oil tourism, destination governance, and regenerative tourism. The analysis identifies four governance challenges: fragmented stakeholder coordination, uneven territorial distribution of benefits, insufficient integration of climate and biodiversity concerns, and limited institutionalisation of monitoring indicators. The article proposes an Oleo-Governance Framework built around five pillars: territorial public value, collaborative destination governance, circular and low-carbon visitor experiences, community capability building, and evidence-based adaptive management. The findings contribute to public administration and tourism planning by showing how a rural destination can use food heritage and landscape identity to advance economic diversification, cultural continuity, and ecological responsibility.